The life and works of Robert Wood : classicist and traveller (1717-1771) - Finnegan, Rachel (Archaeological lives., 2022)
'The Life and Works of Robert Wood' commemorates the Irish classicist and traveller on the 250th anniversary of his death and provides the general reader with a source book for the fascinating life and career of a much-neglected figure in the realm of Irish eighteenth-century travels and antiquarianism.